ПРОФЕСІЙНА КОМПЕТЕНТНІСТЬ СУЧАСНОГО ВЧИТЕЛЯ ОБСЛУГОВУЮЧОЇ ПРАЦІ (Педагогіка вищої та середньої школи, 2008)
In the article the question of study of problem of professional competence of modern huu her of labour studies is examined on the basis of personality - the oriented technology of. For of the best preparation of specialist an author offers application of project technology which will allow to untie the put tasks.